The effect of technology transfer factors on performance: an empirical study of Libyan petroleum industry - Mohamed, Al Mabruk S.; Salit, Mohd Sapuan; Megat Ahmad, Megat Mohamad Hamdan; Hamouda, Abdel Magid Salem; Baharudin, B. T. Hang Tuah (Science Publications, 2009)
Problem statement: In Libya, like most petroleum producing countries, attempts began to develop the petroleum industry through several frames of Technology Transfer (TT). The realization of TT is progressively more forecasted with a starting point of essential factors mainly government support, Knowledge base, environment, Willingness to learn and anticipated to rely more on these factors further in the future. Approach: This study evaluated the degree of significance for the government support, knowledge base, environment and the willingness to learn after years of implementing industry standards, importing technology and training employees and joint ventures with advanced companies were applied to the Libyan petroleum industry. Results: The TT performance factor measurements were derived from a questionnaire survey conducted recently on the Libyan petroleum industry, which involved in TT process. With response rate of 68.35%, the findings showed that the TT performance correlates with the level of readiness of environment, knowledge base, willingness to learn factors and the influential role of government support factor in the Libyan petroleum industry. Conclusion: Hence, results implied or even established that successful performance of TT, which able to cultivate petroleum industry employees can provide a broader spectrum of benefits to the petroleum industry.